Measuring Helpful Aspect of User Experience: The Development of Q-iCalH - Ahmad, Siti Zulaiha; Abdul Mutalib, Ariffin (Springer, Singapore, 2018)
This paper enlightens the development of an instrument to measure helpful aspect of user experience in interactive computer-assisted learning for low achieving children courseware, namely, iCAL4LA-Bijak Matematik. The iCAL4LA-Bijak Matematik is a working prototype that has been developed based on the conceptual design model of interactive computer-assisted learning for low achieving children in primary school. The instrument was developed in the context of children-tailored questionnaire, named as questionnaire of interactive computer-assisted learning helpfulness (Q-iCalH), which presented in two versions (for the low achieving (LA) children and the facilitator). It contains 11 measuring items that elicited from 12 previous works. This study engaged with 11 experts for content and face validity tests. This study manages to test the instrument, n = with 64 low achieving children from year one to year three. Having conducted the validity and reliability tests, this study found that the instrument is consistent and reliable (α = 0.816) in measuring helpful aspect of user experience.